Innovation and finance: An SFC analysis of great surges of development - Alessandro Caiani; Antoine Godin; Stefano Lucarelli (Levy Economics Institute of Bard College, 2012)
Schumpeter, a century ago, argued that boom-and-bust cycles are intrinsically related to the functioning of a capitalistic economy. These cycles, inherent to the rise of innovation, are an unavoidable consequence of the way in which markets evolve and assimilate successive technological revolutions. Furthermore, Schumpeter's analysis stressed the fundamental role played by finance in fostering innovation, in defining bank credit as the monetary complement of innovation. Nevertheless, we feel that the connection between innovation and firm financing has seldom been examined from a theoretical standpoint, not only by economists in general, but even within the Neo-Schumpeterian research line. Our paper aims at analyzing both the long-term structural change process triggered by innovation and the related financial dynamics inside the coherent framework provided by the stock-flow consistent (SFC) approach. The model presents a multisectoral economy composed of consumption and capital goods industries, a banking sector, and two household sectors: capitalists and wage earners. The SFC approach helps us to track the flows of funds resulting from the rise of innovators in the system. The dynamics of prices, employment, and wealth distribution among the different sectors and social groups is analyzed. Above all, the essential role of finance in fostering innovation and its interaction with the real economy is underlined.
Keywords: E11; E32; O31; 330; Schumpeter; Innovation; Stock-flow Consistent Models; Monetary Circuit